Synthesis, Configurational Analysis, Molecular Recognition and Chirality Sensing of Methylene‐Bridged Naphthotubes - Wang, Yan‐Fang; Yao, Huan; Yang, Liu‐Pan; Quan, Mao; Jiang, Wei (Angewandte Chemie International Edition, 2022)
Macrocyclic hosts with a well‐defined cavity are particularly appealing for supramolecular chemistry, but they are still rare. In this research, we reported a new class of macrocyclic hosts, namely methylene‐bridged naphthotubes, with well‐defined cavities. They were synthesized through TFA‐catalyzed Friedel–Crafts reactions between alkoxy‐substituted bisnaphthalenes and paraformaldehyde. A configurational selection was observed. Three‐membered macrocycles possess a single cavity, while four‐membered macrocycles adopt a double‐cavity conformation or a self‐filling conformation depending on the alkoxy length. The small homologue shows quite strong binding affinities (up to 108 M−1) to organic cations, which is better than structurally similar but flexible macrocycles. This demonstrates the advantage of a well‐defined cavity in molecular recognition. Moreover, these naphthotubes can be used as chirality sensors for chiral organic cations through different chirality transfer mechanisms. Methylene‐bridged naphthotubes have been successfully developed. The three‐membered naphthotubes possess a rigid and well‐defined cavity, while four‐membered naphthotubes possess a double‐cavity conformation or a self‐filling conformation depending on the alkoxy length. They show quite strong binding affinities (up to 108 M−1) to organic cations and can be used as chirality sensors for chiral organic cations.